Associations Between Residential Greenness and Adverse Birth Outcomes: A National Study of Canadian Women. (June 2017) - Villeneuve, Paul; Lam, Sandy; Stieb, David; Crouse, Daniel; Tjepkema, Michael; Pinault, Lauren; Osornio-Vargas, Alvaro; Zaiane, Osmar; Hystad, Perry; Jerrett, Michael; Beckerman, Bernardo; van Donkelaar, Aaron; et al.
Abstract : Background: During the past decade several studies have observed that increased vegetation or 'greenness' around mothers' residences is associated with healthier birth weights. However, for the most part, these studies did not take into account the potential confounding role of air pollution, nor evaluated other birth outcomes. Methods: We examined associations between pregnancy outcomes and measures of residential greenness among 2.2 million singleton live births among all census metropolitan areas in Canada between 1999 and 2008. Pregnancy outcomes included: preterm birth, small for gestational age, and birth weight. Environmental exposures to greenness, fine particulate matter, and nitrogen dioxide were assigned to the postal code of place of residence of the mother at the time of birth. Exposure to greenness was based on the Normalized Difference Vegetation Index, while estimates of PM2.5 and NO2were estimated using remote sensing, and a national land-use regression model, respectively. Multivariable regressions were conducted to characterize associations between residential greenness and the birth outcomes, and stratified analyses done by neighbourhood measures of socio-economic status. Results: Mothers' who lived in greener areas had lower risks of preterm birth,  low birth weight and small for gestational age. These associations persisted after adjustment for ambient NO2 and PM2.5. Specifically, in fully adjusted models, an interquartile range (IQR=0.16) increase in greenness yielded odds ratios of 0.93 (95% CI= 0.92, 0.94), 0.94 (95% CI= 0.92, 0.95), and 0.94 (95% CI=0.93, 0.95) for preterm birth, low birth weight, and small for gestational age respectively. Similarly, an IQR increase in greenness was also associated with a 16.3g (95%=CI 15.3, 17.4) increase in birthweight. Stratified analyses by neighbourhood income indicated that there were beneficial impacts of residential greenness on birth outcomes across all income categories. Conclusions: The findings of this population-based national study support the hypothesis that residential proximity to vegetation contributes to healthier pregnancies.